PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA MENGGUNAKAN PENDEKATAN PROBLEM SOLVING - Muliana Muliana (Jurnal Dedikasi Pendidikan, 2017)
The purpose of the research in the design of this pseudo experiment investigated the improvement of students' math problem solving skills using problem solving approach. This research was conducted at State Elementary School 3 Seunuddon as many as 40 students. This research is an experimental study with one group pre-test-post-test design. The population in this study were all students of class V (five) by taking samples of two classes through random sampling technique. Data obtained through math problem solving test. Data were analyzed with Anava. Before used Anava first test homogeneity in research and normality in this study with a significant level of 5%.The result of data analysis shows that F on learning factor of Problem Solving and Learning Approach is 15,930 with significance value 0.000 smaller than level of significance 0,05 so Ho is rejected.Thus it can be concluded that there is an increase in problem solving skills of students using Problem Solving Approach is significantly better than that of students with ordinary learning.The researcher suggests: (1) in order to model the Problem Solving Approach to be an alternative for teachers in improving students' math problem solving abilities (2) learning tools are well prepared and adapted to capability indicators and time allocations to be achieved (3) to be selective in choosing materials Is taught by Problem Solving Approach because not all suitable material is applied with Problem Solving Approach